2000
DOI: 10.1046/j.1440-1819.2000.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal loss and neurofibrillary degeneration in the hippocampal cortex in late‐onset sporadic Alzheimer's disease

Abstract: To explore more fully the relationship between neuronal death and neurofibrillary degeneration, unaffected neurons, intracellular neurofibrillary tangles (i-NFT) and extracellular NFT (e-NFT) in 22 patients with late-onset sporadic Alzheimer's disease (AD) were morphometrically evaluated in eight subdivisions of the hippocampal cortex, using the Gallyas hematoxylin-eosin stain. The subdivisions examined included CA4, CA3, CA2, CA1 (CA: cornu ammonis), prosubiculum (PRO), subiculum and presubiculum (PRE), paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 17 publications
4
47
0
Order By: Relevance
“…The reduction in ␣ 1D -AR mRNA cannot be attributed to the cell loss documented in the CA1 in AD (Simic et all., 1997;Bobinski et al, 1998;Fukutani et al, 2000;Price et al, 2001;Rossler et al, 2002) because ␣ 2A -AR mRNA expression was unchanged in the same region, in the same subjects. It is possible that these different ␣-AR subtypes are expressed in different neurons and the neurons expressing ␣ 1D -AR mRNA are lost in AD and DLB.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The reduction in ␣ 1D -AR mRNA cannot be attributed to the cell loss documented in the CA1 in AD (Simic et all., 1997;Bobinski et al, 1998;Fukutani et al, 2000;Price et al, 2001;Rossler et al, 2002) because ␣ 2A -AR mRNA expression was unchanged in the same region, in the same subjects. It is possible that these different ␣-AR subtypes are expressed in different neurons and the neurons expressing ␣ 1D -AR mRNA are lost in AD and DLB.…”
Section: Discussionmentioning
confidence: 89%
“…Perhaps the loss of ␣ 2C -AR mRNA in AD and DLB subjects in the hippocampus contributes to these behavior symptoms. The loss of ␣ 2C -AR mRNA in the GCL or CA3 cannot be attributed to neuronal loss in AD because these regions do not demonstrate any degree of loss (Simic et al, 1997;Bobinski et al, 1998;Fukutani et al, 2000;Price et al, 2001;Rossler et al, 2002), and the expression of ␣ 2A -AR mRNA in the same regions was unchanged in AD and DLB.…”
Section: Discussionmentioning
confidence: 99%
“…Neurofibrillary tangles, a defining feature of Alzheimer's disease (AD), occur earlier and with much greater frequency in the superficial layers of perirhinal and entorhinal cortex than in most areas of neocortex (Brun and Gustafson, 1976;Ball, 1977;Braak andBraak, 1985, 1991;Arnold et al, 1991;Casanova et al, 1993;Arendt et al, 1998;Braak et al, 2000). Regional differentiation is also well documented for the hippocampus, where tangles are significantly more frequent in CA1 than in CA3 neurons (Braak and Braak, 1991;Bobinski et al, 1996;Corder et al, 2000;Fukutani et al, 2000). Aberrant swellings of the initial segments of axons ("meganeurites"), a feature that occurs with increasing frequency in human brains beginning at about age 50, also show a striking regional selectivity (e.g., layer III but not layer V of the frontal cortex), which matches well with the distribution of tangles (Braak, 1984).…”
mentioning
confidence: 99%
“…AD is characterized by a well-defined progression of its histopathological hallmarks amyloid plaques and neurofibrillary tangles. Particularly the latter has been shown to be closely associated with cognitive performance and neuron loss within the hippocampus and mesio-temporal lobe (Giannakopoulos et al, 1996;Giannakopoulos et al, 2007;Fukutani et al, 2000). The earliest site of neurofibrillary tangle accumulation in the preclinical state of AD is the trans-entorhinal cortex (BA 35) followed by the entorhinal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is not a homogeneous structure but consists of several histologically and functionally specialized but nonetheless tightly interconnected subfields: the subiculum (SUB) which is subdivided into the prosubiculum, subiculum proper, pre-and parasubiculum, the cornu ammonis sectors (CA) 1-3 and the dentate gyrus (DG) (Duvernoy et al, 2013). Animal and histopathological studies have shown that different pathological conditions affect subfields differently, e.g., Alzheimer's disease and hypoxia damage CA1, schizophrenia CA2, traumatic brain injury and post-traumatic stress syndrome CA3 and temporal lobe epilepsy damages the dentate gyrus (e.g., West et al, 1994;Fukutani et al, 2000;Bluemcke et al, 1999;Lucassen et al, 2006;Baldwin et al, 1997;Bluemcke et al, 2007). These observations suggest that subfield specific information might allow for a better differentiation of different disease processes and consequently for an earlier diagnosis than total hippocampal volume (Small, 2014).…”
Section: Introductionmentioning
confidence: 99%